2021
DOI: 10.3847/1538-4365/ac205a
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Nitrogen Isotope Ratios: New NH3 Data from the Galactic Center out to the Perseus Arm

Abstract: Our aim is to measure the interstellar 14N/15N ratio across the Galaxy, to establish a standard data set on interstellar ammonia isotope ratios, and to provide new constraints on the Galactic chemical evolution. The (J, K) = (1, 1), (2, 2), and (3, 3) lines of 14NH3 and 15NH3 were observed with the Shanghai Tianma 65 m radio telescope (TMRT) and the Effelsberg 100 m telescope toward a large sample of 210 sources. One hundred fourty-one of these sources were detected by the TMRT in 14NH3. Eight of them were als… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…Figure 6 shows estimated 14 N/ 15 N ratios as a function of galactocentric distance. If we adopt an assumption of constant 12 C/ 13 C abundance ratio of 89, 14 N/ 15 N abundance ratios tend to increase with galactocentric distance, which is consistent with the 14 N/ 15 N gradient found in the Milky Way (Dahmen et al 1995;Adande & Ziurys 2012;Romano & Matteucci 2003;Romano et al 2017;Chen et al 2021).…”
Section: The 12 C/ 13 C Abundance Ratiosupporting
confidence: 79%
See 1 more Smart Citation
“…Figure 6 shows estimated 14 N/ 15 N ratios as a function of galactocentric distance. If we adopt an assumption of constant 12 C/ 13 C abundance ratio of 89, 14 N/ 15 N abundance ratios tend to increase with galactocentric distance, which is consistent with the 14 N/ 15 N gradient found in the Milky Way (Dahmen et al 1995;Adande & Ziurys 2012;Romano & Matteucci 2003;Romano et al 2017;Chen et al 2021).…”
Section: The 12 C/ 13 C Abundance Ratiosupporting
confidence: 79%
“…This ratio measured in two starbursts, NGC 4945 (∼200-400, Henkel et al 2018) and ULIRG Arp 220 (440 +140 −82 , Wang et al 2014), are higher than those found in M 82 (∼ 80 − −250, see Figure 6). In our Milky Way, the 14 N/ 15 N ratios distribute in a large range (100-600, Li et al 2017), with a possible positive gradient from the center to out disk (Chen et al 2021).…”
Section: The 12 C/ 13 C Abundance Ratiomentioning
confidence: 96%
“…Figure 6 shows estimated 14 N/ 15 N ratios as a function of galactocentric distance. If we adopt an assumption of a constant 12 C/ 13 C abundance ratio of 89, 14 N/ 15 N abundance ratios tend to increase with galactocentric distance, which is consistent with the 14 N/ 15 N gradient found in the Milky Way (Dahmen et al 1995;Romano & Matteucci 2003;Adande & Ziurys 2012;Romano et al 2017;Chen et al 2021).…”
Section: The 12 C/ 13 C Abundance Ratiosupporting
confidence: 78%
“…This ratio measured in two starbursts, NGC 4945 (∼200-400, Henkel et al 2018) and ULIRG Arp 220 (440 +140 −82 , Wang et al 2014), is higher than found in M82 (∼80-250, see Figure 6). In our Milky Way, the 14 N/ 15 N ratio is distributed in a large range (100-600, Li et al 2017), with a possible positive gradient from the center to the outskirts (Chen et al 2021).…”
Section: The 12 C/ 13 C Abundance Ratiomentioning
confidence: 99%
“…We are performing systematic observational studies on isotope ratios in the Milky Way, including 12 C/ 13 C (Yan et al 2019), 14 N/ 15 N (Chen et al 2021), 18 O/ 17 O (Zhang et al 2015(Zhang et al , 2020a(Zhang et al , 2020bLi et al 2016), and 32 S/ 34 S (Yu et al 2020). We have thus performed a more systematic study on CS and its isotopologs toward 110 high-mass star-forming regions (HMSFRs).…”
Section: Introductionmentioning
confidence: 99%